Praktik Arisan (Barang) di Desa Karangtengah Kecamatan Ampelgading Pemalang Ditinjau dari Hukum Ekonomi Syariah - Aji, Gunawan; Utami, Lutfi Ayu Fadhilah (Fakultas Syariah IAIN Kerinci, 2023)
The research aims to find out the law of arisan goods in terms of Islamic economic law. The way of thinking of this research is inductive thinking, namely drawing conclusions from various facts and references. The analysis technique is carried out by collecting data, selecting data and simplifying, presenting data and drawing conclusions based on the facts and references sought. From the research it can be concluded that there are two views between the permissibility and prohibition of arisan goods seen from an Islamic perspective, namely the opinion of scholars based on the Koran, as sunnah and sharia economic law. However, the weak opinion that forbids arisan causes arisan goods to be allowed with conditions. The conditions are that there must be an agreement contract, prioritizing justice and honesty.